THE ROLE OF ENTREPRENEURSHIP EDUCATION IN PRODUCING YOUNG ENTREPRENEURS - Rahmawati Alwi; Muhammad Daffa Munadhil; Rusdi Khairuddin; Syahrul Rhamdhani; Ibn Pahriji; Irvan Fahrul Rozi (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
Entrepreneurship education has a strategic role in facing the challenges of unemployment and the low interest of the younger generation in the business world. Through entrepreneurship education, students are equipped with knowledge, skills, and mental attitudes that encourage independence and creativity. This study aims to analyze the role of entrepreneurship education in producing independent, innovative, and competitive young entrepreneurs. The research method used is a qualitative approach with literature study techniques and descriptive analysis of various relevant literature sources. The results of the study show that entrepreneurship education is able to form an entrepreneurial mindset, improve risk-taking skills, and foster creativity and courage to do business in the younger generation. Entrepreneurship education that is applied systematically and contextually also contributes to building a strong character and orientation to business opportunities. The conclusion of this study emphasizes that entrepreneurship education plays an important role as a strategic means in producing young entrepreneurs who are ready to face economic challenges in the modern era.